Family Experiences in Caring for a Stroke Patient with Decubitus Ulcer at Home - Nur Chayati; Rahmadani, Wahyudi (Public Health of Indonesia, 2024)
Background: The role of the family in caring for stroke patients with decubitus ulcers requires them to assist in meeting daily needs such as nutrition, elimination, personal hygiene, and mobilization. While caring for a stroke patient with decubitus ulcers, the family experiences significant burdens that also impact the family's physical, social, and psychological, activities, and financial conditions. Objective: To gain a deep understanding of the family's experience in caring for a stroke patient with decubitus ulcers at home. Methods: This research uses a qualitative design with a phenomenological study approach. The selection of participants using a purposive sampling technique. The number of participants in this study was 8 people with family criteria who had a family member of stroke with decubitus ulcer and were treated at home. The data in this study were collected through semi-structured interviews, audio recorders, and field note. The data analysis test used is the Collaizi method. Results: The research analysis found three themes, namely Theme 1: Physical, psychological, social, and financial barriers experienced by caregivers while caring for stroke patients with decubitus ulcers. Theme 2: The role of family caregivers in helping basic needs: eating and drinking, personal hygiene, elimination, mobilization. Theme 3: The type of treatment chosen by the caregiver based on the family's financial condition. Conclusion: Family experience in caring for stroke patients who experience decubitus ulcers has a role in helping to meet the basic needs of patients, some obstacles are also experienced by families such as physical, psychological, and financial. This obstacle also affects families in choosing the type of treatment given to patients.